Holistic Health Care based on Moderate Postmodern Philosophy - Thongjun, Sudthinee; Takaew, Ravich; Bunchua , Kirti; Amalitwarin, Sirikorn (Buddhamagga, 2022)
The problems of caring and promoting the physical, mental, psycho-social, spiritual, intellectual, and environmental health to protect health before, between, and after the illness are the holistic health care problems. This study was the philosophical research aiming at interpreting the holistic health care based on Paradigm Philosophy 5, and at appreciating and applying the holistic health care based on the moderate postmodern philosophy. The results showed that the holistic health care based on the moderate postmodern philosophy was a concept focusing on health self-reliance by means of care and prevention of illness that did not reduce self-esteem, had no adherence, had discretion and sympathy in order to develop oneself to enhance the secure and sustainable happiness, and to access to the true value of life. The application involved: 1) care and promotion of physical health by preventing the diseases and illness by self-immunization; 2) care and promotion of mental health by paying attention to intellectual activities, and by explaining causes of behaviors; 3) care and promotion of psycho-social health by relationship coordination, which would result to well-being and learning how to live together in the society securely; 4) care and promotion of spiritual health by having belief, faith, and understanding in humans’ original and genuine mind under a condition of the existence in this present world and the future world; 5) care and promotion of intellectual health by studying to have the complete knowledge and understanding and to feel confident in causes and reasons occurred; and 6) care and promotion of environmental health by care for physical, mental, psycho-social, spiritual, and intellectual health along with the care for all things supporting health under balance and harmony. The Thai society has engaged various traditional and cultural origins succeeded so long. Therefore, Thai people’s health care must rely on their belief, respect, and faith. The holistic health care in the Thai society context has several methods. Individuals’ viewpoints could be used to care for the holistic health under balance and harmony, which could lead to the secure and sustainable well-being.